Assessment Of Adverse Childhood Experiences Among In-School Adolescents in Lagos State - Ojo , Taiye Emmanuel; Akintola , Aderonke Adebola; Animashaun , Paul Oluwaseyi (Corpus Intellectual, 2025)
Adverse Childhood Experiences (ACEs) refer to potentially traumatic events that can negatively affect a person’s general health and well-being and have become increasingly recognised as a public health concern. Hence, the current study aimed to assess the prevalence of ACEs among in-school adolescents in Lagos State. A descriptive, cross-sectional research design was employed, with both purposive and convenience sampling techniques used to recruit 516 in-school adolescents, 251 males (48.6%) and 265 females (51.4%) from three selected secondary schools in Alimosho local government area of Lagos State. The participants responded to the Childhood Trauma Questionnaire (CTQ). Their mean age was 15.02±1.56 years, and an overall 92.5% prevalence rate of adverse childhood experiences was found among these adolescents; 3.1% reported severe ACEs, while 38.8% and 50.6% reported moderate and severe ACEs, respectively. Physical abuse was 42.8%, emotional abuse 86.9% and sexual abuse 32.6%. Both physical and emotional neglect constituted a prevalence rate of 90.5% each. Also found were significant relationships among the components of ACEs- physical abuse, sexual abuse, emotional abuse, physical neglect and emotional neglect. Further analysis revealed that the minimisation/denial, which indicates the tendency to present an overly positive view of childhood using psychological defence mechanisms, was low among the adolescents, with 26.9% having no denial, 28.5% with low denial, 34.5% were moderate, and 10.1% high in denial tendency respectively. This study concluded that there is a high prevalence of adverse childhood experiences among in-school adolescents in Lagos State. They are a serious burden to these adolescents. Therefore, timely psychological interventions should be provided to those who have experienced or are experiencing ACEs.